2021
DOI: 10.1029/2020jc016583
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Anthropogenic Activity and Sea‐Level‐Rise in Tidal Distortion on the Open Coast of the Yellow Sea Shelf

Abstract: This study investigates how varied coastline strategies and rising mean‐sea‐level influence tidal distortion along the open coast of the Yellow Sea shelf. The major contributors to tidal distortion were first identified. Then, the primary tidal constituents causing changes in tidal propagation and distortion in response to shoreline reconstruction management and near‐future sea‐level‐rise (SLR) were determined. The intrinsic mechanisms causing tidal duration asymmetry (TDA) were investigated and found to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…If g 1 >0, the periods of flood tides are shorter than those of ebb tides, and conversely, if g 1 <0, the periods of ebb tides are shorter than those of flood tides. Furthermore, to quantify the contribution of different combinations of tidal constituents to TDA, Song et al (2011) derived a general framework for evaluating TDA by substituting Equation (2) into Equation (4), which is expressed as (Feng and Feng, 2021):…”
Section: Analysis Of Tdamentioning
confidence: 99%
See 2 more Smart Citations
“…If g 1 >0, the periods of flood tides are shorter than those of ebb tides, and conversely, if g 1 <0, the periods of ebb tides are shorter than those of flood tides. Furthermore, to quantify the contribution of different combinations of tidal constituents to TDA, Song et al (2011) derived a general framework for evaluating TDA by substituting Equation (2) into Equation (4), which is expressed as (Feng and Feng, 2021):…”
Section: Analysis Of Tdamentioning
confidence: 99%
“…The sets of Equation ( 5) demonstrate that TDA can be generated or canceled only by interactions between two harmonic constituents with a frequency relationship 2w 1 =w 2 or among three constituents with a frequency relationship w 1 +w 2 =w 3 . Moreover, introducing b as the weight of TDA from the skewness caused by a specific pair or triplet of tidal constituents, the total TDA is equal to the cumulative effects of b (Feng and Feng, 2021):…”
Section: Analysis Of Tdamentioning
confidence: 99%
See 1 more Smart Citation
“…Feng and Feng [81] explored the influence of coastline changes and a rising sea level on tidal asymmetry along the coast of Jiangsu and found that the interactions between M 2 /M 4 and M 2 /S 2 /MS 4 were most sensitive to coastline changes and contributed the largest part to tidal distortion. Using ROMS, Lin et al [9] studied the tidal response to changes in coastline and water depth related to land reclamation and waterway dredging in the Pearl River Estuary (PRE).…”
Section: Changing Tides Under Natural Variability and Human Activitiesmentioning
confidence: 99%